Vehicular Engine Design - Hoag, Kevin; Dondlinger, Brian; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2016)
This book provides an introduction to the design and mechanical development of reciprocating piston engines for vehicular applications. Beginning from the determination of required displacement and performance, coverage moves into engine configuration and architecture. Critical layout dimensions and design trade-offs are then presented for pistons, crankshafts, engine blocks, camshafts, valves, and manifolds.  Coverage continues with material strength and casting process selection for the cylinder block and cylinder heads. Each major engine component and sub-system is then taken up in turn, from lubrication system, to cooling system, to intake and exhaust systems, to NVH. For this second edition latest findings and design practices are included, with the addition of over sixty new pictures and many new equations.
The internal combustion engine -- an introduction.-  Engine maps, customers and markets -- Engine validation and durability -- Considerations in engine development -- Determining displacement -- Engine configuraton and balance -- Cylinder block and head materials and manufacturing -- Block layout and design decisions -- Cylinder head layout design -- Block and head development -- Engine bearing design -- Engine lubrication -- Engine cooling -- Gasket and seals -- Pistons and rings -- Crankshafts and connecting rods -- Camshafts and the valve train.
Keywords: Automotive engineering; Automotive Engineering